Maternal postpartum corticosterone and fluoxetine differentially affect adult male and female offspring on anxiety-like behavior, stress reactivity, and hippocampal neurogenesis. (February 2016) - Gobinath, Aarthi R.; Workman, Joanna L.; Chow, Carmen; Lieblich, Stephanie E.; Galea, Liisa A.M.
Abstract: Postpartum depression (PPD) affects approximately 15% of mothers, disrupts maternal care, and can represent a form of early life adversity for the developing offspring. Intriguingly, male and female offspring are differentially vulnerable to the effects of PPD. Antidepressants, such as fluoxetine, are commonly prescribed for treating PPD. However, fluoxetine can reach offspring via breast milk, raising serious concerns regarding the long-term consequences of infant exposure to fluoxetine. The goal of this study was to examine the long-term effects of maternal postpartum corticosterone (CORT, a model of postpartum stress/depression) and concurrent maternal postpartum fluoxetine on behavioral, endocrine, and neural measures in adult male and female offspring. Female Sprague–Dawley dams were treated daily with either CORT or oil and fluoxetine or saline from postnatal days 2–23, and offspring were weaned and left undisturbed until adulthood. Here we show that maternal postpartum fluoxetine increased anxiety-like behavior and impaired hypothalamic-pituitary-adrenal (HPA) axis negative feedback in adult male, but not female, offspring. Furthermore, maternal postpartum fluoxetine increased the density of immature neurons (doublecortin-expressing) in the hippocampus of adult male offspring but decreased the density of immature neurons in adult female offspring. Maternal postpartum CORT blunted HPA axis negative feedback in males and tended to increase density of immature neurons in males but decreased it in females. These results indicate that maternal postpartum CORT and fluoxetine can have long-lasting effects on anxiety-like behavior, HPA axis negative feedback, and adult hippocampal neurogenesis and that adult male and female offspring are differentially affected by these maternal manipulations. Highlights: Maternal postpartum fluoxetine increased anxiety-like behavior in adult males. Maternal postpartum fluoxetine impaired HPA axis negative feedback in adult males. Maternal postpartum fluoxetine raised neurogenesis in males but reduced in females. Maternal postpartum CORT increased neurogenesis in males but decreased in females. Maternal postpartum corticosterone blunted HPA axis activity in males and females.